Oposisi Anwar Ibrahim Dan Politik Malaysia - Herdi Sahrasad (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2015)
Anwar Ibrahim's political future to lead Malaysia is more opened. Nevertheless, there is no guarantee that he wins the coming election. On behalf of the opposition alliance he leads, Anwar will launch his campaign for the Justice Party, and he would join hands with the pluralists and Chinese race-based parties in Malaysia. In one posting on Twitter on 9/1/2012, Anwar vowed to overthrow the Malaysian government, what the so-called a corrupt regime Under Anwar Ibrahim's opposition movement, there is a strong tendency that the livelihood of Malaysian society, especially in the field of political education, is experiencing a stage of "silent reform" (reform silently) that is structured and led by the educated middle class with the main objective to uphold democracy, clean and good governance.